Analysis of Physics Assessments Designed by Science Teachers at Junior High School - Febriyanti Suryaningsih; Judyanto Sirait; Naim Sulaiman (Jurnal Penelitian Pembelajaran Fisika, 2025)
This study aims to analyze the suitability of physics assessments designed by science teachers at the junior high school level by paying attention to good assessment criteria. This type of research is descriptive-qualitative, involving three teachers in junior high school.  The data collection technique is in the form of assessment archive documentation. The assessment analyzed was divided into three documents, namely motion and force, simple aircraft and static electricity. Data analysis techniques are in the form of data reduction, data presentation and conclusion drawn. The design of an assessment needs to pay attention to several aspects in it, namely the suitability of learning objectives to learning outcomes, the suitability of the competencies given, the use of language, the assessment rubric and the answer key in the assessment. Based on the results of the analysis, the assessment designed has included learning objectives, competencies, and achievement indicators. However, some aspects still need improvement, such as the use of operational verbs (KKO) in learning objectives, language consistency, and the completeness of the assessment rubric and answer key. These results show that the assessment has not fully met the optimal criteria to support learning evaluation.